Penyelesaian Sengketa Bedrog (Penipuan) Dalam Perjanjian Jual Beli Kayu: Onrechtmatige Daad Atau Wederrechtelijk? (Studi Kasus: Putusan Mahkamah Agung Nomor: 449K/Pid/2001) - Anindita, Sri Laksmi; Sitanggang, Eriska Fajrinita (UI Scholars Hub, 2022)
Criminalization Of Civil Disputes Is A Common Case In Indonesia. This Case Can Occur Because An Act Or Action May Violate Two Laws At The Same Time, Those Are Civil Law And Criminal Law. The Intersection Between A Civil Dispute And A Criminal Act Does Not Only Make The Borderline Between Civil And Criminal Cases Thin. Settlement Of Disputes Over Acts That Contain Elements Of Fraud Arising From A Contractual Relationship Through Civil Law Mechanisms By Filing A Lawsuit (Onrechtmatige Daad Or Default) Or Criminal Law Mechanisms (Wederrechtelijk), Is Often Confusing. How To Determine An Act With An Element Of Fraud Is Included In The Domain Of Criminal Or Civil Law And How To Resolve Disputes That Arise As A Result Of Fraud In A Timber Sale And Purchase Agreement (Case Study: Supreme Court Decision Number: 449k/Pid/2001), Is The Formulation Of The Problem, Which Will Be Discussed In This Paper Using Normative Legal Research Methods. Settlement Of Disputes Resolution Through A Criminal Case For An Act Containing Fraud Elements In A Timber Sale And Purchase Agreement (Case Study: Supreme Court Decision Number: 449k/Pid/2001) Is Incorrect. Settlement Of Disputes That Arise In This Case Must Be Resolved By Filing A Civil Claim.